2018
DOI: 10.1007/s00192-018-3618-2
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking behaviour for pelvic floor dysfunction in women over 55: drivers and barriers

Abstract: Women are more likely to seek help for PFD if scoring higher on the APFQ or symptoms are becoming more bothersome. They are less likely to seek help if they view their symptoms as normal. Future direction should be taken to raise awareness of normal pelvic floor function as well as the availability of help for PFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 25 publications
(39 reference statements)
4
45
1
Order By: Relevance
“…Indeed, relationship status was positively associated with help-seeking in women but not men. Again, this could reflect gender-role socialisation in that heterosexual women are encouraged to maintain harmony within their relationship (Stoppard and McMullen 2003), and one way to do this is to put the relationship first. Similarly, women from three countries, compared to (a very small percentage of) men from one country cited a reason for seeking professional help as fear of their partner seeking another sexual partner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, relationship status was positively associated with help-seeking in women but not men. Again, this could reflect gender-role socialisation in that heterosexual women are encouraged to maintain harmony within their relationship (Stoppard and McMullen 2003), and one way to do this is to put the relationship first. Similarly, women from three countries, compared to (a very small percentage of) men from one country cited a reason for seeking professional help as fear of their partner seeking another sexual partner.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients consider their primary care physician a generalist rather than a specialist, and for this reason older adults do not see them as an appropriate source of help for sexual issues (Sarkadi and Rosenqvist 2001). This is an important finding as other studies have identified that the primary care physician would be the first port of call for older adults who wanted help for a sexual difficulty (Gott and Hinchliff 2003b;Tinetti et al 2018). Other reasons why older adults do not seek help for a sexual difficulty include viewing the problem as a "normal" part of ageing (Moreira et al 2005;Tinetti et al 2018), feeling comfortable with how things are, waiting to see if it got better on its own, and not viewing the difficulty as serious (Moreira et al 2005).…”
Section: Seeking and Receiving Helpmentioning
confidence: 99%
“…This suggestion of broad potential reach, especially among women who already use the Internet for health information and among women with a higher BMI, is especially important because obesity is a barrier to care seeking for incontinence. 18 Given that stigma is a known barrier to seeking medical health care for bowel 19,20 and bladder incontinence, 21,22 it is not surprising that the desire for privacy drove women's preference for the online format. Respondents offered suggestions to improve accountability and skill building and to incorporate an interactive forum option to overcome some of the disadvantages of an online program.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the higher percentage of women with FSFI scores indicating sexual dysfunction (63.3%). According to the literature, increased level of symptom bother is the main factor for seeking medical help among women with PFD [25]. Tinetti et al reported sexual dysfunction in as many as 77.9% of women with PFD aged over 55 years [25].…”
Section: Discussionmentioning
confidence: 99%